(untitled) (Gaceta Técnica, 2021)
Humanity has taken a great turn, the appearance of Covid-19 forced the populations of the different hemispheres to modify their way of life, education and work. Abruptly the schemes changed, adaptation was required immediately. It is there when the breaking point appears, and the question arises, was society prepared for all this? Professional training now has a new vision, the modification of the appropriate study plans every 5 or 10 years is no longer viable; A new paradigm becomes evident, the awareness of the need to act for a now and an after in order to ensure a healthy growth of the population, is fundamental. Civil engineering careers, as well as architecture and urban planning, cannot remain static in the face of the unpredictable and circumstantial, it is already seen that humanity is fragile.